First Click Eye Tracking A/B Tests of Web-Page Interactive Elements - Julia FALKOWSKA; Janusz SOBECKI (Communications of International Proceedings, 2020)
Eyetracking metrics can be calculate and analyze in user experience web sites evaluation. This paper presents the results from the experiment where 11 commercial websites where tested with first click A/B tests. Used methodology are user observation and eyetracking data recording. Aim of the study is to verify the legitimacy of the use and interpretation of a specific set of eye-tracking metrics for the purpose of their universal application in user experience research on websites.
Keywords: eye tracking; user experience; eyetracking metrics; A/B tests